Hypervalent Iodine-Based Activation of Triphenylphosphine for the Functionalization of Alcohols - Eljo, Jasmin; Carle, Myriam S.; Murphy, Graham K. (Synlett, 2017)
The use of hypervalent iodine reagents as a general tool for the activation of PPh3 and its application to the functionalization of alcohols is reported. Combination of PPh3 with PhICl2 or TolIF2 gives dihalophosphoranes that are characterized by 31P NMR, however, with PhIOAc2, PhI(OTFA)2, or the cyclic chloro(benzoyloxy)iodane, no phosphoranes were observed. Reaction of these iodanes with PPh3 in the presence of primary, secondary, or tertiary alcohols results in either halogenation or acyl-transfer products in moderate to high yield.
Keywords: Appel reaction; hypervalent iodine; halogenation; acylation; benzoylation